Advances in Pancreatic Ductal Adenocarcinoma Treatment - Eric M. Anderson (MDPI AG, 2021)
Pancreatic Ductal Adenocarcinoma (PDAC) is one of the deadliest malignancies among all cancers. Despite curative intent, surgery and the use of standard cytotoxic chemotherapy and radiation therapy, PDAC remains treatment-resistant. In recent years, more contemporary treatment modalities such as immunotherapy via checkpoint inhibition have shown some promise in many other malignancies, yet PDAC still eludes an effective curative treatment. In investigating these phenomena, research has suggested that the significant desmoplastic and adaptive tumor microenvironment (TME) of PDAC promote the proliferation of immunosuppressive cells and act as major obstacles to treatment efficacy. In this review, we explore challenges associated with the treatment of PDAC, including its unique immunosuppressive TME. This review examines the role of surgery in PDAC, recent advances in surgical approaches and surgical optimization. We further focus on advances in immunotherapeutic approaches, including checkpoint inhibition, CD40 agonists, and discuss promising immune-based future strategies, such as therapeutic neoantigen cancer vaccines as means of overcoming the resistance mechanisms which underly the dense stroma and immune milieu of PDAC. We also explore unique signaling, TME and stromal targeting via novel small molecule inhibitors, which target KRAS, FAK, CCR2/CCR5, CXCR4, PARP and cancer-associated fibroblasts. This review also explores the most promising strategy for advancement in treatment of pancreatic cancer by reviewing contemporary combinatorial approaches in efforts to overcome the treatment refractory nature of PDAC.